2014
DOI: 10.1039/c4ra09153a
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of 2-substituted quinolines and 3-alkynyl-2-aryl-2H-Indazole via SnCl2-mediated reductive cyclization

Abstract: COMMUNICATIONThis journal is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 50 publications
(10 reference statements)
2
21
0
Order By: Relevance
“…The reductive variant of the heterocyclization, which was described by Patil and Raut, [96] was proposed four years later by Sudhapriya et al [97] . The one‐pot two‐step strategy for the coupling of 2‐nitrobenzaldehydes 143 , piperidine 91 and alkynes 3 , which involves the sequential treatment of the mixture with 10 mol% CuI in refluxing toluene and then with 4 equiv.…”
Section: Synthesis Of Six‐membered N‐heterocyclesmentioning
confidence: 99%
See 1 more Smart Citation
“…The reductive variant of the heterocyclization, which was described by Patil and Raut, [96] was proposed four years later by Sudhapriya et al [97] . The one‐pot two‐step strategy for the coupling of 2‐nitrobenzaldehydes 143 , piperidine 91 and alkynes 3 , which involves the sequential treatment of the mixture with 10 mol% CuI in refluxing toluene and then with 4 equiv.…”
Section: Synthesis Of Six‐membered N‐heterocyclesmentioning
confidence: 99%
“…It is worth noting that the use of aromatic amines instead of piperidine in this process leads to a change in the chemoselectivity of the reaction, resulting in the formation of ethynylindazoles 148 (Scheme 45). Sudhapriya et al [97] . suggested that propargylamines 149 generated from anilines undergo incomplete reduction of the nitro group to the nitroso group (intermediate 150 ).…”
Section: Synthesis Of Six‐membered N‐heterocyclesmentioning
confidence: 99%
“…A substituted 2H-indazole synthesis via SnCl 2 mediated reductive cyclization was reported by Perumal and co-workers in 2014 via RuÀ Cu catalysis (Scheme 57). [59] The use of mild and effective catalysts, cheap and stable starting materials, and ordinary reaction conditions are the advantages of the reaction. This metal-catalyzed multicomponent reaction proceeds with the formation of N-aryl propargylamine by an A3 coupling reaction between ortho-nitrobenzaldehyde, aniline, and phenylacetylene in the presence of CuBr and RuCl 3 .…”
Section: Re-catalyzed Synthesismentioning
confidence: 99%
“…A substituted 2 H ‐indazole synthesis via SnCl 2 mediated reductive cyclization was reported by Perumal and co‐workers in 2014 via Ru−Cu catalysis (Scheme ) . The use of mild and effective catalysts, cheap and stable starting materials, and ordinary reaction conditions are the advantages of the reaction.…”
Section: Sn‐mediated Synthesismentioning
confidence: 99%
“…[29][30][31][32][33][34][35][36] What's confusing is that 8-hydroxyquinolines were rarely involved in these reports. [37][38][39][40] Considering the importance in pharmacology and functional materials chemistry, the development of more facile and economic synthetic approached for 8-hydroxyquinolines is highly desirable.…”
Section: Introductionmentioning
confidence: 99%